1999
DOI: 10.1159/000057468
|View full text |Cite
|
Sign up to set email alerts
|

Intradialytic Parenteral Nutrition in Malnourished Hemodialysis Patients. Review of the Literature

Abstract: Malnutrition is a frequent problem of patients on intermittent hemodialysis and is associated with increased morbidity and mortality. Intradialytic parenteral nutrition (IDPN), i.e. intravenous supplementation of mixtures of glucose, amino acids and/or lipids during the hemodialysis session, is one of the therapeutic measures that are applied to correct this malnutrition. To our knowledge only few long-term clinical studies have been undertaken, evaluating the effect of intravenous calorie administration in he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2002
2002
2010
2010

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 32 publications
(53 reference statements)
0
5
0
Order By: Relevance
“…Treatment of this problem includes increasing oral nutritional intake and the use of oral dietary supplements designed for patients with chronic kidney disease (Koppler 1999; Bossola et al 2005). However, this is sometimes unsuccessful, whereas in other patients oral/enteral feeding is inadequate to meet daily nutrient requirements (Mortelmans and Vanholder 1999). It is in these patients that intradialytic parenteral nutrition (IDPN) may offer an additional source of both protein and calories (Serna‐Thorme et al 2002).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Treatment of this problem includes increasing oral nutritional intake and the use of oral dietary supplements designed for patients with chronic kidney disease (Koppler 1999; Bossola et al 2005). However, this is sometimes unsuccessful, whereas in other patients oral/enteral feeding is inadequate to meet daily nutrient requirements (Mortelmans and Vanholder 1999). It is in these patients that intradialytic parenteral nutrition (IDPN) may offer an additional source of both protein and calories (Serna‐Thorme et al 2002).…”
Section: Introductionmentioning
confidence: 99%
“…For over 30 years nephrologists have argued over the indications for IDPN (Mortelmans and Vanholder 1999; Foulks 1999; Cano 2004). In 1999, Hakim wrote, ‘malnourished dialysis patients are at a very high risk for morbidity and mortality.…”
Section: Introductionmentioning
confidence: 99%
“…Despite the continuing progress in renal replacement therapies, protein calorie malnutrition (PCM) and wasting are frequent problems in patients on chronic hemodialysis (HD) [1], representing strong predictors of morbidity and mortality [2]. The etiology of PCM in patients on HD can be caused by multiple combinations of factors such as reduced food ingestion, metabolic changes, inadequate dialysis adequacy, or bioincompatibility of the membranes [2].…”
Section: Introductionmentioning
confidence: 99%
“…Protein deficiency has been detected as one of the main nutritional problems, especially due to its severe clinical consequences. Several studies have demonstrated the adverse effects of small decreases in serum albumin on the survival of patients on maintenance HD [1, 5, 6]. In parallel, the HD procedure itself can induce an increase in total body proteolysis [7] and remove nutrients, with the loss of amino acids, dipeptides and proteins through the dialysate [8,9,10,11,12].…”
Section: Introductionmentioning
confidence: 99%
“…One frequently used intervention in ESRD patients suffering from malnutrition is IDPN. The benefit, however, is still under debate (Siskind and Lien, 1993;Capelli et al, 1994;Mortelmans and Vanholder, 1999;Pupim et al, 1999;Stenvinkel et al, 2000).…”
Section: Discussionmentioning
confidence: 99%